2023
DOI: 10.2174/1573403x19666221220163431
|View full text |Cite
|
Sign up to set email alerts
|

Mitral Valve Prolapse and Sudden Cardiac Death in Athletes at High Risk

Abstract: Mitral valve prolapse (MVP) is the most frequent valvulopathy in the general population, with usually a favourable prognosis. Although it can be associated with some complications, ventricular arrhythmias (VA) and sudden cardiac death (SCD) are the most worrying. The estimated risk of SCD in MVP is between 0.2% to 1.9% per year, including MVP patients with and without severe mitral regurgitation (MR). The association between SCD and MVP is expressed by a phenotype called “malignant MVP” characterized by transt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 83 publications
(107 reference statements)
0
1
0
Order By: Relevance
“…In most cases, MVP has a benign course (in the absence of moderate-to-severe/severe MR, LV dysfunction/dilation, or an AMVP phenotype), and it does not imply any sports restriction in asymptomatic athletes [ 100 ]. Furthermore, a recent retrospective study demonstrated the lack of association between lifetime exercise dose and severe VA or high-risk phenotypic features in MVP patients and that severe Vas most often occur at rest in AMVP patients, therefore suggesting the opportunity to encourage MVP patients to practice moderate intensity exercise, defined by the authors as a total lifetime exercise dose below the threshold of 9.6 MET h/week [ 30 ].…”
Section: Sports Eligibility Assessment and Therapymentioning
confidence: 99%
“…In most cases, MVP has a benign course (in the absence of moderate-to-severe/severe MR, LV dysfunction/dilation, or an AMVP phenotype), and it does not imply any sports restriction in asymptomatic athletes [ 100 ]. Furthermore, a recent retrospective study demonstrated the lack of association between lifetime exercise dose and severe VA or high-risk phenotypic features in MVP patients and that severe Vas most often occur at rest in AMVP patients, therefore suggesting the opportunity to encourage MVP patients to practice moderate intensity exercise, defined by the authors as a total lifetime exercise dose below the threshold of 9.6 MET h/week [ 30 ].…”
Section: Sports Eligibility Assessment and Therapymentioning
confidence: 99%